Tongue diagnosis indices for gastroesophageal reflux disease: A cross-sectional, case-controlled observational study. Issue 29 (17th July 2020) - Wu, Tzu-Chan; Lu, Cheng-Nan; Hu, Wen-Long; Wu, Keng-Liang; Chiang, John Y.; Sheen, Jer-Ming; Hung, Yu-Chiang
Abstract : Abstract: Traditional Chinese medicine tongue diagnosis can mirror the status of the internal organ, but evidence is lacking regarding the accuracy of tongue diagnosis to gastroesophageal reflux disease (GERD). This study was to investigate the association between GERD and tongue manifestation, and whether tongue imaging could be initial diagnosis of GERD noninvasively. We conducted a cross-sectional, case-controlled observational study at Kaohsiung Chang Gung Memorial Hospital in Taiwan from January 2016 to September 2017. Participants aged over 20 years old with GERD were enrolled and control group without GERD were matched by sex. Tongue imaging were acquired with automatic tongue diagnosis system, then followed by endoscope examination. Nine tongue features were extracted, and a receiver operating characteristic (ROC) curve, analysis of variance, and logistic regression were used. Each group enrolled 67 participants. We found that the saliva amount ( P  = .009) and thickness of the tongue's fur ( P  = .036), especially that in the spleen–stomach area (%) ( P  = .029), were significantly greater in patients with GERD than in those without. The areas under the ROC curve of the amount of saliva and tongue fur in the spleen–stomach area (%) were 0.606 ± 0.049 and 0.615 ± 0.050, respectively. Additionally, as the value of the amount of saliva and tongue fur in the spleen–stomach area (%) increased, the risk of GERD rose by 3.621 and 1.019 times, respectively. The tongue fur in the spleen–stomach area (%) related to severity of GERD from grade 0 to greater than grade B were 51.67 ± 18.72, 58.10 ± 24.60, and 67.29 ± 24.84, respectively. The amount of saliva and tongue fur in the spleen–stomach area (%) might predict the risk and severity of GERD and might be noninvasive indicators of GERD. Further large-scale, multi-center, randomized investigations are needed to confirm the results. Trial registration: NCT03258216, registered August 23, 2017.